Photochemically controlled synthesis of anisotropic Au nanostructures : platelet-like Au nanorods and six-star Au nanoparticles - Huang, Xiao (2012)
We report the shape-controlled synthesis of anisotropic Au nanostructures through TiO2-assisted photochemical reduction of HAuCl4. By using this method, we have successfully synthesized the platelet-like Au nanorods and six-star Au nanoparticles. Importantly, the platelet Au nanorod exhibits the unique asymmetric five-twinned structure. The colloidal TiO2 sols were used as both the photocatalyst to initiate the reaction and the stabilizing agent for the produced Au nanostructures. Significantly, in this photochemical process, the tunable irradiation intensity allows us to kinetically control the crystal evolution at various growth stages, leading to the shape difference of ultimate gold nanostructures. Our synthetic method shows a great potential as an alternative or supplement to the other wet chemical approaches for the shape-control of metallic nanostructures.